Paradoxes of Digital Disengagement: In Search of the Opt-Out Button - Adi Kuntsman; Esperanza Miyake (University of Westminster Press, 2022)
Life is increasingly governed and mediated through digital and smart technologies, platforms, big data and algorithms. However, the reasons, practices and impact of how the digital is used by different institutions are often deeply linked to social oppression and injustice. Similarly, the ability to resist these digital impositions is based on inequality and privilege. Challenging the ways in which we are increasingly dependent on the digital, this book raises a set of provocative and urgent questions: in a world of compulsory digitality is there an opt out button? Where, when, how, why and to whom is it available? Answering these questions has become even more relevant since the COVID-19 pandemic. In response, the book puts forward the concept of 'digital disengagement' which is explored across six key areas of digitisation: health; citizenship; education; consumer culture; labour; and the environment. Part I examines the difficulty of opting out of compulsory digitality in a world where most things are digital by default. From health apps, algorithmic decision-making to learning analytics, opting out comes with a set of troubling consequences. Part II turns to several examples of disconnection and disengagement. The chapters reveal how phenomena like digital detoxes, time-management apps and online 'green' spaces are co-opted by the very digital systems one is trying to resist. The book critiques issues relating to digital surveillance, algorithmic discrimination and biased tech, corporatisation and monetisation of data, exploitative digital labour, digitalised self-discipline and destruction of the environment. As an interdisciplinary piece of work, the book will be useful to any scholar and activist in Digital, Internet and Social Media Studies; Digital Sociology and Social Policy; Digital Health; Media, Popular and Communication Studies; Consumer culture; and Environment Studies.
Keywords: 320; Platform Society; Digital Disengagement; Digital Abolition; COVID-19 Pandemic; Data Rights and Data Justice; Digital Capitalism